Evaluation of newly combination of Trichoderma with dimethyl disulfide fumigant to control Fusarium oxysporum, optimize soil microbial diversity and improve tomato yield - Zhaoai Shi; Min Zhang; Guangming Chen; Aocheng Cao; Qiuxia Wang; Dongdong Yan; Wensheng Fang; Yuan Li (Ecotoxicology and Environmental Safety)
This study focuses on the severe soil-borne disease problems resulting from the continuous tomato cultivation in China, with the aim of deeply studying the multi-dimensional effects of the combined application of dimethyl disulfide (DMDS) and Trichoderma on soil microecology and tomato yield. Firstly, a plate confrontation experiment was conducted in the laboratory to determine the antibacterial effect of Trichoderma afroharzianum (TAF), and the results indicated that the inhibition rate of TAF against Fusarium oxysporum, an important tomato soil-borne pathogen, was 70.8 %, which suggests TAF could be a potential biocontrol agent. Subsequently, in tomato greenhouses in Fangshan, Beijing, DMDS (60 g/m2) was utilized to fumigate the soil before planting, and then T. afroharzianum (TAF) and Trichoderma harzianum (THZ) were applied for root irrigation of the seedlings during tomato growth. By monitoring the variations in soil microbial communities and resistance to gray mold, it was found that the addition of Trichoderma (TAF and THZ) could effectively inhibit the growth of soil-borne pathogens and significantly reduce the occurrence of gray mold, thereby significantly enhancing tomato yield, with an average increase of 11.5 %. High-throughput sequencing results demonstrated that the addition of Trichoderma suspension after fumigation had a significant impact on bacterial microbial communities, increasing the abundance of beneficial bacteria and fungi such as Truepera, Kernia, Agronomyces, Tumebacillus, and Acidibacter, optimizing the structure of soil microbial communities and promoting the healthy and sustainable development of soil and microecosystems. Moreover, some bacteria exhibit outstanding capabilities in degrading chemical substances in the soil, offering a robust guarantee for restoring the original healthy state of the soil. In conclusion, the research results explicitly demonstrate that the combined application of DMDS and biological agents constitutes a highly effective new approach to overcome soil succession obstacles, providing an innovative control strategy for the precise management of tomato soil-borne diseases.